Issues In Teaching English To Speakers Of Other Languages (Tesol): A Review Of Literature - Murtiningsih, Sri Rejeki (Lingua Cultura, 2011)
The article aims to review English language teaching to speakers of other languages and other related aspects such as the use of technology and the first language in classroom practices. As the need for English language competency develops, efforts to support students’ learning also change. In addition to the teaching techniques, the technology development has also gained attention for improving effective teaching and learning. Because English is a language that is not used in daily communication and the variety of students’ language competence, the use of first language in a foreign language classroom has also become another point to encourage the students’ foreign language acquisition.